PENGENDALIAN PERSEDIAAN BAHAN BAKU KEMASAN SEMEN DENGAN METODE LAGRANGE MULTIPLIER (Studi Kasus : PT. X) - M. Agus Rivai; Dwi Sukma D; Urip Widodo (Jurnal Ilmiah Dinamika Teknik, 2019)
X is one of manufactur plan for produceof cement facilities. The problems found in the company are still the condition of overstock or excess inventory of raw materials which results in swelling of inventory costs. This study aims to provide an optimal amount of raw material inventory so as to minimize total inventory costs and determine the savings in raw material inventory costs. The effort to control raw material inventory uses the Lagrange Multiplier method so that the research objectives are achieved. The object of this study was on the SWEN Cement Packaging which experienced Overstock. Conclusions obtained optimal order for Woven Lamination of 212.2 tons, Kraft (Kenner Paper) of 257.78 and Neolin Yarn of 50.81, with a Total Cost (TCQ * Li) Lagrange Multiplier produced at Rp.554.360.200 -From the calculation results obtained that the total inventory costs by the Lagrange Multiplier method amounted to Rp. 554.360.200, - while the initial total cost was Rp. 726.105.000, which resulted in savings of 23.66%.